STRATEGIC INTERESTS AND POWER BALANCES: A REALIST ANALYSIS OF THE US-SAUDI ALLIANCE AMIDST NEW GLOBAL RIVALRIES - Shahkar Mehdi; Muntazir Mehdi; Fathi F Elsied Elfaghri; Saleem Arshad Chheena; Arbaz Raza (International Journal of Contemporary Issues in Social Sciences, 2024)
The paper examines the stable strategic alliance between Saudi Arabia and the United States through the lens of Realist framework, amid the evolving global power dynamics. It explores the historical context of the alliance, emphasizing the mutual interests that have sustained it over years. The research employs qualitative methodology, considering state-level interactions and its implications for regional rivalries and global shifts in power dynamics. The findings reveal that despite new challenges, the alliance remains a keystone of geopolitical strategy, driven by confluence of security, economic, and political factors. The paper concludes with recommendations for policy makers in both states, suggesting adaptive strategies to direct the complexities of current international relations.